Neurophysiological Changes Induced by Chronic Toxoplasma gondii Infection - Tedford, Ellen (Pathogens, 2017)
Although the parasite Toxoplasma gondii is one of the most pervasive neurotropic pathogens in the world, the host-parasite interactions during CNS infection and the consequences of neurological infection are just beginning to be unraveled. The chronic stages of infection have been considered dormant, although several studies have found correlations of infection with an array of host behavioral changes. These may facilitate parasite transmission and impact neurological diseases. During infection, in addition to the presence of the parasites within neurons, host-mediated neuroimmune and hormonal responses to infection are also present. T. gondii induces numerous changes to host neurons during infection and globally alters host neurological signaling pathways, as discussed in this review. Understanding the neurophysiological changes in the host brain is imperative to understanding the parasitic mechanisms and to delineate the effects of this single-celled parasite on health and its contribution to neurological disease.